The Girls and the Others: Racialized Anthropomorphism in the First Season of The Powerpuff Girls - Jalen Thompson (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2019)
The Powerpuff Girls (1998) chronicles the lives of three kindergarten-aged girls with superpowers. Blossom, Bubbles, and Buttercup were conceived in a laboratory by a scientist, Professor Utonium, out of “sugar, spice, and everything nice” with an accidental spill of “Chemical X” which in turn gives the girls their superpowers to “fight the forces of evil.” As protectors of Townsville, the suburban community in which they reside, each episode shows the girls battling with various villains (usually men) who are established as outsiders to Townsville. The villains are represented as ethnic minorities through racialized anthropomorphism which associates their evilness to their ethnicity. The girls’ fight against “the forces of evil,” then, is a fight keep to maintain a society in which ethnic minorities are not welcome, conveying racist and classist messages. In this paper, I argue that Creator Craig McCracken produces a series in which places white male figures—Professor Utomium and the narrator—establish a white, middle-class, patriarchal society, or a “Townsvillian” society, that the girls must maintain. In a series that appears to pass as a girl power text, the stereotyped representations of the villains relate the series with problematic and less progressive messages, ultimately making it a non-feminist text.
Keywords: The Powerpuff girls; girl power; race; class; children' s animation